KOMPARASI METODE SIMPLE ADDITIVE WEIGHTING DAN WEIGHTED PRODUCT PADA PEMILIHAN VENDOR BEARING TURBIN DI PT. AZ - Galih Aditya Pangestu; Nina Aini Mahbubah; Purwanto Purwanto (Fakultas Teknik, Universitas Riau Kepulauan, 2026)
This study aims to compare and contrast the Simple Additive Weighting (SAW) and Weighted Product (WP) methods in supplier selection at a power generation company. The firm challenge with a problem that supplier selection process that remains subjective and based on a single criterion, namely price. This study applies a descriptive quantitative approach using data from fifteen suppliers evaluated on five criteria: price, lead time, quality, delivery accuracy, and capacity. Each step of the SAW and WP methods is systematically described from decision matrix construction, This study aims to compare and contrast the Simple Additive Weighting (SAW) and Weighted Product (WP) methods in supplier selection at a power generation company. The firm challenge with a problem that supplier selection process that remains subjective and based on a single criterion, namely price. This study applies a descriptive quantitative approach using data from fifteen suppliers evaluated on five criteria: price, lead time, quality, delivery accuracy, and capacity. Each step of the SAW and WP methods is systematically described from decision matrix construction, normalization, to ranking. The results show that both methods yield identical top three rankings, namely suppliers S11, S12, and S14. Ranking differences in two pairs of alternatives with close values. Both methods yield consistent decisions and can serve as an objective basis for supplier selection, to ranking. The results show that both methods yield identical top three rankings, namely suppliers S11, S12, and S14. Ranking differences in two pairs of alternatives with close values. Both methods yield consistent decisions and can serve as an objective basis for supplier selection